PEMBENTUKAN KARAKTER KEWIRAUSAHAAN PESERTA DIDIK MELALUI KEGIATAN EKSTRAKURIKULER PRAMUKA PADA SMP NEGERI 7 KECAMATAN TUALANG KABUPATEN SIAK - E R N I ' (Program Studi Pendidikan Ekonomi Universitas Riau, 2017)
The purpose of the research is the establishment of enterprenuerial character inlearners at SMP Negeri 7 Tualang in district of Tualang Siak. Data obtained from thefollowing sources such as head master, teacher’s (scoutmaster), and student’s.Subfocus of this research is the programs and activities of scouting, scoutingprogram which has charge of entrepreneurship, entrepreneutial character formationof students is done through the scouting program and factors inhibiting andsupporting the establishment of entrepreneurial character through scouting activities.Data collected by observation, interview, field notes, and study documentation. Datahave been obtained, then analyzed by systematically compile the data obtained. Theresult of this research SMP Negeri 7 Tualang can set-up 17 characters value ofentrepreneurial learners. Through a training program and coaching of scoutmaster,learners are able to carry out the practices of entrepreneurship.